Households Community Preparedness in Dealing with Landslides - Ridwan Pauji, Muhammad; Maryani, Enok; Ruhimat, Mamat (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
The aim of this research were to (1) identify household preparedness in dealing with landslides as seen from the indicator of knowledge and attitude, emergency planning, early warning system resources mobilizing capability, (2) to analyze factors of difference household preparedness. Research was done to the society of Cipanas subdistrict, Cianjur district, West Java. The method used is descriptive. Sampling was done by purposive sampling study with the number of 72 households in each sample area. The data analysis used an index analysis to measure the level of household preparedness. The results of early research shows that level of household preparedness in dealing with landslide in Cipanas subdistrict, district of Cianjur, is still in the low category. The values of each parameter are vary, but overall fall into the less prepared category.